Sculptures on the doorframe of the Entrance Gateway - Temples of India Project Team (Jio Institute, 2024)
The lower portion of the doorframe of the entrance gateway, of the Mahanaleshwar temple complex, is detailed and has three sculptures: one attendant and two river goddess figures. Below these sculptures is the ratnapatta (plinth with diamond motif).